The Brain as Myth: Cinematic Representations and Mythic Reproduction in the Korean Science Fiction Film Jung_E - Lee, Soojin; Yoon, Nara (International Journal of Korean Humanities and Social Sciences, 2025)
Science fiction films emerge from contemporary developments in science and technology, creating narratives through the integration of humanistic imagination. They also serve as essential bridges for understanding the scientific concerns and aspirations of each era. Since the 2010s, the Korean film industry has witnessed a rise in the production of SF works that engage with issues such as artificial intelligence, robotics, aerospace technology, and genetic engineering. However, these films have not achieved notable success with neither audiences nor critics, despite their growing number. The cause of this phenomenon lies in the attitude of many Korean filmmakers, who often display limited interest in scientific and technological domains. As a result, they fail to meaningfully explore the complex relationship between evolving technological environments and human existence. Director Yeon Sang-ho’s Jung_E exemplifies this problematic tendency. Jung_E incorporates advanced technologies such as AI and robotics, yet these elements remain largely decorative – they do not constitute the core of the narrative. This superficial engagement with science and technology leads to fundamental misrepresentations; for instance, the film’s flawed portrayal of memory and intelligence becomes embedded in its cinematic representations of AI. To investigate this issue, this article draws on Roland Barthes’s theory of mythology as its analytical framework. It further adopts an interdisciplinary approach that integrates insights from the natural sciences with semiotic analysis. Through this methodology, the study demonstrates how Korean SF films weaken their artistic potential by sidelining scientific thinking and adhering to mythologized views of science and technology.